The Role of Transition Metal Dopants in Controlling the Electronic Defects in Hematite (Α-Fe2O3) Under Different Thermodynamic Conditions - El Gibally, Hoda Essam Salah El Din (AUC Knowledge Fountain, 2022)
Hematite is one of the most environmentally friendly and cost-effective materials that has distinguished intrinsic properties ,which qualifies it to be involved in the manufacturing process of many important technological applications. On the other hand, hematite has some limiting factors ,which can immensely constraint its usage, such as its low electronic conductivity. Though iron interstitials at extremely reducing condition can provide hematite with n-type conductivity, reaching these extremely low oxygen partial pressures (p ) values is not practical in many cases, especially from an industrial perspective where mass production is required. Therefore , it is highly recommended to find alternative defects that can supply excess electrons to hematite, but at reasonable thermodynamical conditions .This can be accomplished by the addition of donor dopants. Hence, this study targeted monitoring the changes in the concentrations of electronic defects ,especially electrons, under different p conditions ,upon the addition of 1% of 15 selected transition metal (TM) dopants . The dopants include the whole 3d TM family in addition to Zr,Nb and Mo from the 4d TMs and Hf,Ta and W from the 5d TMs . The formation energies of all defects ,both dopant and intrinsic , were calculated using first-principles density-functional theory (DFT) simulations , where these formation energies were used as raw data for plotting the Kröger Vink diagrams (KVDs) which are isothermal plots of the defect concentrations vs. oxygen partial pressure. The KVDs are plotted at 1100 K , which is a common sintering temperature for hematite, to quantitatively investigate the concentration of all possible dopant defects , including substitutional and interstial defects, where the latter is rarely investigated in the literature. A new algorithm was proposed in order to provide a robust and accurate method for plotting KVDs in the presence of fixed doping level, highlighting the previously reported methods and their limitations compared to our newly propsed approach. The plots provided insights on the compensation mechanism through which either enhancements or deteriorations of electronic charge carriers occured in doped hematite . More importantly, the plots were used to identify the highest p value at which the dopant provides at least an equivalent number of electrons to its own. This value was considered as the limiting p condition for successful donor dopant implementation. Furthermore, the limiting p values for each dopant were used to filter out successful donor dopants ,which provide excess electrons at reasonable p conditions that are ~ atm or higher. The results showed that Ti , Zr ,Ta ,Hf ,Mo ,W, and Nb can be used as effective donor dopants for hematite, whereas the remaining 3d transition metals did not demostrate a significant enhacement to the electron’s density. Out of all effective donor dopants , W , Nb, and Ta achieved the best results , providing a one electron/dopant ratio around atmospheric pressure at 1100 K. Moreover, these three dopants provided the maximum electron/dopant ratios, where the later quantity was introduced for the first time in this work and was used as another metric for assessing the perfromance of dopants as donors. For W doped hematite, the reported maximum electron/dopant ratio was around 2.6-2.7 at atm p ,whereas for Ta and Nb doped hematite, the ratio was 1.9 at atm p , where all values were reported at 1100 K. Moreover , a co-doping study was perfromed , where the total concentrations of both dopants was fixed to 1% and the enhancements in the concentrations of electrons as well as holes was observed. The results demonstrated no enhencement in the electrons’ density for any pair of the investigated dopants compared to the single doping results of the better dopant in the pair. Despite of that, W , Ta and Nb maintained their high electron densities even when co-doped with other non effective donor dopants.This can be profitable when these three elements are codoped with other dopants , which control other properties in hematite and hence this co-doping can provide other benificial properties for hematite, in addition to enhanced conductivity . On the contrary , the co-doping of the best achiever donors W, Ta, Nb and Mo with Zn acceptor resulted in a hole’s density enhancement versus its single donor dopant coutnerpart, while preserving the required electron/dopant ratio at an acceptable p range .The concentration of holes around atmospheric pressure at 1100 K was enhaced by 1.85 times for W-Zn co-doping,whereas it was enhaced by 1.42 times for Ta/Nb-Zn co-doping, and by 1.24 times for Mo-Zn co-doping.These enhancements should be very benificial for hematite when used in applications where holes are the limiting factor such as in the photoelectrochemical water splitting devices. The presented study can be used to guide experimentalists to the optimum donor dopants that best enhance the electron’s density in hematite . In addition to recommending the most convenient thermodynamica doped hematite preparation conditions to obtain the required enhancements. Furthermore, realizing dopants that provide conductivity enhancements at atmospheric pressure can have substantial effects on reducing manufacturing costs ,which make these hematite doped materials ideal for scalable production for a wide range of applications.